(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes the cellular and molecular causes of cancer, including genetic mutations, oncogenes, intracellular signaling pathways, and disruptions in apoptosis processes. It also examines the biological characteristics of cancer cells and the potential for early detection using molecular methods. The article discusses the biological basis for early diagnosis and personalized approaches to cancer diagnostics, focusing on biomarkers and genetic tests.